Impact of hyaluronic acid on healing of cold wounds - Seliuta, Anatolii; Kovalov, Gennadiy; Poliakova, Hanna; Gurina, Tetiana (Problems of Cryobiology and Cryomedicine, 2025)
Probl Cryobiol Cryomed 2025; 35(4):242